2021
DOI: 10.1021/acsapm.1c00197
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Interfacial Properties in Polymer–Silica Nanocomposites via Surface Modification: An Atomistic Simulation Study

Abstract: Surface modification is an effective way to improve the dispersion of nanofillers in a polymer matrix and tune the interfacial interactions that determine macroscopic properties in polymer nanocomposites. In this work, we present a detailed investigation of silane modification effects on polymer interfacial conformation and dynamic properties through atomistic molecular dynamics simulations, using cis-1,4 polyisoprene (the major component of natural rubber) and amorphous silica substrate as a model system. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Simulations at different temperatures may require further refinement of the models and, more importantly, time-scaling mapping (related to friction) . Our coarse graining methodology presents significant potential for applications to systems with higher complexity, such as random copolymers and composite materials, ,, which will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Simulations at different temperatures may require further refinement of the models and, more importantly, time-scaling mapping (related to friction) . Our coarse graining methodology presents significant potential for applications to systems with higher complexity, such as random copolymers and composite materials, ,, which will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Each PI monomer comprises five united atoms, corresponding to CH 2 , C, CH, CH 2 , and CH 3 with the mass of 14.027, 12.011, 13.019, 14.027, and 15.035 Da, respectively. The UA force field was adopted from previous studies showing quantitative agreement with experimental findings on lower molecular weight systems. ,,,, …”
Section: Models and Simulation Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors then reported structural and dynamical properties, such as chain dimensions and the relaxation of the end-to-end vector for the chemistry-specific coarse-grained model [51]. Amorphous silica substrates were also used to confine the polyisoprene chains in thin films [52,53]. In their study, Guseva et al investigated the effect of the film thickness and, thus, of the imposed confinement, reporting mainly the overall properties of the material averaged over the whole film [52].…”
Section: Introductionmentioning
confidence: 99%